2014
DOI: 10.1016/j.hjdsi.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Innovative payment mechanisms in Maryland Hospitals: An empirical analysis of readmissions under total patient revenue

Abstract: Background The state of Maryland implemented innovative budgeting of outpatient and inpatient services in eight rural hospitals under the Total Patient Revenue (TPR) system in July, 2010. Methods This paper uses data on Maryland discharges from the 2009-2011 Healthcare Cost and Utilization Project (HCUP) State Inpatient Databases (SID). Individual inpatient discharges from eight treatment hospitals and three rural control hospitals (n=374,353) are analyzed. To get robust estimates and control for trends in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Using all‐payer hospital claims data and a difference‐in‐difference design, Done and Herring found no changes in admissions, readmissions, or emergency department (ED) visits associated with the program after 3 years, but did find a statistically significant 14.8% reduction in non‐ED outpatient utilization. By and large, these findings echo those of two prior evaluations of Maryland's program in rural hospitals, which found no change in readmissions among all payers after 18 months, and no changes in inpatient and ED use in a Medicare‐only population after 3 years . All three studies of the rural program utilized within‐state comparison groups—comprised of populations served by Maryland hospitals that had yet to receive global budgets—to isolate the effect of hospital budgets from other policy changes unique to Maryland's hospital payment system, providing a robust framework with which to examine the impact of this payment model in rural settings.…”
Section: Global Budgets In Maryland Hospitals: Assessing the Evidencesupporting
confidence: 65%
“…Using all‐payer hospital claims data and a difference‐in‐difference design, Done and Herring found no changes in admissions, readmissions, or emergency department (ED) visits associated with the program after 3 years, but did find a statistically significant 14.8% reduction in non‐ED outpatient utilization. By and large, these findings echo those of two prior evaluations of Maryland's program in rural hospitals, which found no change in readmissions among all payers after 18 months, and no changes in inpatient and ED use in a Medicare‐only population after 3 years . All three studies of the rural program utilized within‐state comparison groups—comprised of populations served by Maryland hospitals that had yet to receive global budgets—to isolate the effect of hospital budgets from other policy changes unique to Maryland's hospital payment system, providing a robust framework with which to examine the impact of this payment model in rural settings.…”
Section: Global Budgets In Maryland Hospitals: Assessing the Evidencesupporting
confidence: 65%
“…Our results are important given the mixed findings of prior analyses of Maryland’s program. While an analysis of the global budget policy in rural hospitals found no differential change in readmissions after 18 months, 13 a study of the statewide program reported differential reductions in hospital admissions and increases in emergency department visits among Medicare beneficiaries. 14 However, this study’s estimates could have been biased by different pre-intervention trends in its control versus intervention populations.…”
Section: Discussionmentioning
confidence: 97%
“…One study, which focused on rural Maryland hospitals, found no change in readmissions attributable to the program, but only examined trends over an 18-month post-intervention period. 13 Other evaluations assessed changes in utilization after Maryland’s statewide expansion of hospital global budgets in 2014. 14,15 However, differences in pre-reform trends between Maryland and these studies’ control groups made it difficult to attribute subsequent changes in utilization to global budgets.…”
mentioning
confidence: 99%
“…However, two studies identified decreases in non-ED outpatient utilization after Total Patient Revenue implementation (Done et al, 2019; Pines et al, 2019). Three studies found no changes in readmission rates after rural hospitals adopted global budgets in 2010 (Done et al, 2019; Mortensen et al, 2014; Roberts, Hatfield, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%